2007
DOI: 10.1073/pnas.0706504104
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous behavior of the density of water in the range 30 K < T < 373 K

Abstract: The temperature dependence of the density of water, (T ), is obtained by means of optical scattering data, Raman and Fourier transform infrared, in a very wide temperature range, 30 < T < 373 K. This interval covers three regions: the thermodynamically stable liquid phase, the metastable supercooled phase, and the low-density amorphous solid phase, at very low T. From analyses of the profile of the OH stretching spectra, we determine the fractional weight of the two main spectral components characterized by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
242
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 228 publications
(283 citation statements)
references
References 38 publications
39
242
1
1
Order By: Relevance
“…In the present experiments, essentially all of the mosaicity increase occurs above 200 K, where the mismatch between solvent expansion and lattice contraction is large (Mallamace et al, 2007). The largest rate of mosaicity increase occurs at temperatures (200-220 K) where the unit-cell volume is rapidly decreasing and the solvent viscosity is rapidly increasing.…”
Section: Origins Of Disorder On Coolingmentioning
confidence: 71%
See 1 more Smart Citation
“…In the present experiments, essentially all of the mosaicity increase occurs above 200 K, where the mismatch between solvent expansion and lattice contraction is large (Mallamace et al, 2007). The largest rate of mosaicity increase occurs at temperatures (200-220 K) where the unit-cell volume is rapidly decreasing and the solvent viscosity is rapidly increasing.…”
Section: Origins Of Disorder On Coolingmentioning
confidence: 71%
“…This mismatch requires that the solvent either flows (to the crystal surface or to grain boundaries and other defective regions where the lattice is weak) or compresses. We estimate that pressures of 10-100 MPa could be generated within the crystal if negligible flow occurs, based upon the observed expansivity of the thaumatin lattice and the measured expansivity of water confined to 2 nm pores (Mallamace et al, 2007). Slower cooling allows more time before vitrification for solvent to flow and to accommodate the contracting protein lattice, and so may reduce stresses and solvent pooling in defective regions and thereby help maintain crystal order.…”
Section: Origins Of Disorder On Coolingmentioning
confidence: 99%
“…4,21 On the other hand, the degree of local order in liquid water will increase with decreasing temperature due to local bond-ordering. 45 A recent FTIR study 46 of the relative populations of high-density liquid (HDL) and low-density liquid (LDL) water in narrow silica pores confirmed that while at temperatures T 4 250 K the structure is dominated by molecules with local HDL order, at lower temperatures (T o 220 K) the molecules of local LDL geometry are dominating. Since the local structure of LDL water resembles that of ice, the freezing process will become an increasingly cooperative phenomenon involving increasingly larger clusters of an ice-like structure, so that freezing will imply the reorganisation of hydrogen bonds only at the periphery of the clusters.…”
Section: Limit Of Crystallization Of Water In Mcm-41mentioning
confidence: 98%
“…Inside the no-man's land, confined water exhibits a density minimum at ∼200 K (experimentally observed in confined water, ref. 30, and suggested in bulk by MD simulations, ref. 31), a C P (T) maximum at ∼230 K, and a α P (T) minimum, also at ∼230 K.…”
mentioning
confidence: 99%
“…The blue ones, corresponding to bulk water, are the same used to fit literature data (25,26). Confined water data also include the C P values measured using normal calorimetry (red dots) (28) and NMR (red triangles) (29), and the density and α P (T) measured using FTIR spectroscopy (17,30) (the density and thermal expansion coefficient data for T < 140 K are for amorphous water). Inside the no-man's land, confined water exhibits a density minimum at ∼200 K (experimentally observed in confined water, ref.…”
mentioning
confidence: 99%